Welcome to the Uzbek-Kazakh Cultural Center! - Mirzayev Nuriddin Faxriddinovich (Genius Journals, 2022)
First of all, this union has been providing us with friendship and co-operation between peoples for a long time. At the same time, we are strengthening relations with peoples through peace in our country and setting an example for the future generation
Keywords: Uzbek-Kazakh Cultural Center; implementation of program; Lyudmila Zyikina; framework of the